City citizenship behavior among residents: Investigating the role of emotional experience in event tourism and brand attitude - Kusumawati, Andriani; Rahayu, Karisma Sri (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2022)
Along with the development of place branding theory, the role of the residents was widely reviewed and considered only as one of the target groups of place branding. Stakeholder involvement in the development of city branding is important because it will support its success. However, in reality, citizens or residents are a group that gains less attention in the city branding strategies and practices. Therefore, this research was developed under the umbrella of branding theory by further analyzing the influence of city brand attitude on city citizenship behavior (CCB) triggered by emotional experiences in tourism events. This explanatory quantitative approach was carried out through a survey by using a questionnaire. A simple random sample was chosen as the sampling method in this study. Data from 323 residents in Malang Raya was collected and analyzed using Partial Least Square (PLS). This study empirically demonstrates that emotional experience in event tourism is likely to stimulate city brand attitude and that subsequent city citizenship behavior among residents is probable. This result allows for understanding a substantial contribution of emotional experience in enhancing positive city brand attitude, finally highlighting the importance of internal stakeholders and their citizenship behavior in the destination branding process.